13.5k views
1 vote
Solve by Substitution

Show Steps
x = −5y + 4z + 1
x − 2y + 3z = 1
2x + 3y − z = 2

1 Answer

7 votes

Answer:

(x, y, z) = (1-z, z, z) . . . . . . . an infinite number of solutions

Explanation:

Use the first equation to substitute for x in the remaining two equations.

(-5y +4z +1) -2y +3z = 1 . . . . substitute for x in the second equation

-7y +7z = 0 . . . . . . . . . . . . . . simplify, subtract 1

y = z . . . . . . . . . . . . . . . . . . . . divide by -7; add z

__

2(-5y +4z +1) +3y -z = 2 . . . . substitute for x in the third equation

-7y +7z = 0 . . . . . . . . . . . . . . subtract 2; collect terms

y = z . . . . . . . . . . . . . . . . . . . . divide by -7; add z

This is a dependent set of equations, so has an infinite number of solutions. Effectively, they are ...

x = 1 -z

y = z

z is a "free variable"

User AlameerAshraf
by
5.6k points